Efficacy of a Self-Hypnotic Relaxation App on Pain and Anxiety in a Randomized Clinical Trial: Results and Considerations on the Design of Active and Control Apps. Issue 2 (3rd April 2021) - Lang, Elvira V.; Jackson, William; Senn, Paul; Aroni, Donavon Khosrow K.; Finkelman, Matthew D.; Corino, Thomas A.; Conway, Graham; Kulich, Ronald J.
ABSTRACT: Despite an explosion of mobile app offerings for management of pain and anxiety, the evidence for effectiveness is scarce. Placebo-controlled trials are the most desirable but designing inactive placebo apps can be challenging. For a prospective randomized clinical trial with 72 patients in a craniofacial pain center, we created an app with self-hypnotic relaxation (SHR) for use with iOS and Android systems. A placebo background audio (BA) app was built with the same look and functionality. Both iOS and Android SHR apps alone and in comparison to the BA group significantly reduced pain and anxiety during the waiting-room time. The Android BA app significantly reduced anxiety but not pain. The iOS BA app affected neither pain nor anxiety, functioning as an ideal placebo. Usage analysis revealed that different default approaches of the iOS and Android devices accounted for the difference in results.